Lexical notes on Mari letters - Arkhipov, Ilya (Zeitschrift für Assyriologie und vorderasiatische Archäologie, 2018)
The present paper identifies new attestations for, and revises the meanings of, some rare words and expressions that appear mainly in Mari letters: baziʔitum ‘(a kind of) monkey’; bêšum ‘to explain, make clear’; ḫarāqum ‘to breach’; ina šārat waṣûm ‘to escape by a hair’s breadth’; kīsum ‘purse’; pāḫātum ‘responsibility’; rabbum ‘chief’; sagûm ‘to wander’; sakānum ‘to settle’; tabākum ‘to throw out’; tarākum ‘to hold aloft’.